What is the underlying structure of the climate, conflict, and socio-economic system in Senegal? A network analysis - Basel, Ashleigh Megan; Onivola Minoarivelo, Henintsoa; Craparo, Alessandro Carmelo William; Läderach, Peter R.D.; Pacillo, Grazia (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Senegal, using network analysis. Results show that high poverty and inequality are key underlying structures in Senegal which determine the path to conflict.